Prevalance and risk factors of congenital malaria in Osogbo, Southwestern Nigeria - Odediji, Saheed A.; Olabanji, Surakat A.; Olawuyi, Abdullahi O.; Amoo, Kazeem O.; Amoo-Adeboye, Basirat O.; Adeleke, Monsuru A. (GMS German Medical Science)
Background: Congenital malaria, defined as the presence of malaria parasites in the peripheral smear of newborns within the first seven days of life, remains an underexplored aspect of malaria epidemiology in endemic regions like Nigeria. This study investigated the prevalence and associated risk factors of congenital malaria at the State Specialist Hospital (SSH), Osogbo, Southwestern Nigeria. Method: This cross-sectional study collected peripheral and cord blood samples from 77 newborns within the first 24 hours of delivery. We examined blood samples for malaria parasites using both light microscopy and malaria rapid diagnostic test (mRDT) kits. A structured research proforma was used to assess various risk factors, including sociodemographic details, gravidity, parity, retroviral status, and malaria prevention measures during pregnancy. Results: The overall prevalence of congenital malaria was 6.5%, with all infants exhibiting congenital malaria also demonstrating cord blood parasitaemia. Maternal malarial parasitaemia emerged as a strong predictive factor (p<0.05), while factors such as maternal retroviral status, intermittent prophylactic therapy, therapeutic antimalarial use, and bednet usage were not significantly associated with congenital malaria (p>0.05). Conclusion: Our study observed a low prevalence of congenital malaria in Osogbo and emphasizes the significance of maternal malarial parasitaemia in predicting the condition. However, there is need for additional multicenter studies to comprehensively determine the prevalence of congenital malaria in Osun State and Nigeria, providing a basis for targeted interventions and healthcare strategies.